Romance phonology and variation : selected papers from the 30th Linguistic Symposium on Romance Languages, Gainesville, Florida, February 2000 - Wiltshire, Caroline R., 1963-; Camps, Joaquim (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2002)
This volume contains a selection of refereed and revised papers, originally presented at the 30th Linguistic Symposium on Romance Languages, focussing on the areas of phonology and language variation. The papers address issues in phonology such as the emergence of the unmarked, representational structure in phonology and morphology, intonation in Spanish, and issues in variation including dialectal differences, codeswitching, foreigner talk, and language death. The papers in this volume include discussions of the major Romance languages (Catalan, French, Italian, Portuguese, Spanish), pidgins.